Structural and Electrical Properties of InSb Films Prepared By Flash Evaporation Technique - Khdayer, Iman Hamed; Alias, Maysoon Faisal Ahmed; Makadsi, Mati Nasir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Indium antimony (InSb) alloy were prepared successfully. The InSb films were prepared by flash thermal evaporation technique on glass and Si p-type substrate at various substrate temperatures (Ts= 423,448,473, and 498 K). The compounds concentrations for prepared alloy were examined by using Atomic Absorption Spectroscopy (AAS) and X-ray fluorescence (XRF). The structure of prepared InSb alloy and films deposited at various Ts were examined by X-ray diffraction (XRD).It was found that all prepared InSb alloy and films were polycrystalline with (111) preferential direction . The electrical properties of the films are studied with the varying Ts. It is found that the electrical conductivity of the films increased with the increase of Ts, while the activation energies decreased. The Hall Effect measurements showed that the type of all prepared films was n-type .The charge carrier concentration decreased with the increase Ts whereas, the carriers mobility increased. The drift velocity, mean free path and life time of the deposited films for all the range of Ts have been determined. From the measurements of the four point probe methods, the sheet conductivity increased with the increase of Ts.